The anxiolytic and antidepressant effect of Buxus hyrcana in the pentylenetetrazole kindled rat - AZIZI, V; ALLAHYARI, F; HOSSEINI, A (Journal of the Hellenic Veterinary Medical Society, 2021)
Pentylenetetrazole (PTZ) is a chemical substance which largely used for induction of seizure and epilepsy in the animal model, and it can also, disrupts free radicals balance and causes oxidative stress in the body with a negative impact on behavioral statuses like anxiety and depression. In this study, the medicinal plant Buxus hyrcana, was used to evaluate its effect on oxidative stress, anxiety and depression caused by PTZ in the rat. Twenty-four male rats were randomly allocated to 4 groups: control negative under treatment with PTZ (sub-threshold dose 35 mg/kg for one month), control positive under treatment with phenobarbital (PB-30 mg/kg), and two PTZ groups under treatment with B. hyrcana extract (BHE-300, and -600 mg/kg). For anxiety parameters, the elevated plus maze (EPM) was used. The forced swim test (FST) and rotarod test were employed to assess the antidepressant and balance potential, respectively. After behavioral evaluation, rats were anesthetized, brains were removed, and following preparation of brain homogenates, oxidative stress was evaluated using specified methods. BHE administered at the doses of 300, and 600 mg/kg, reduced immobility time in the FST exerting antidepressant-like activity. In the EPM test, BHE at the same doses, produced the anxiolytic-like effect. Also, the rats which received BHE had a significant improvement in rotarod test in contrast to control groups. In addition, brain catalase activity and superoxide dismutase level were significantly greater versus PTZ group BHE-300 treated PTZ group was significantly lower and. BHE could prevent anxiety and depression and ameliorate oxidative stress in PTZ-kindled rats.